Comparison on cooling efficiency of cooling pad materials for evaporative cooling system - Radhiyah, Abd Aziz; Nurul Farahin, Zamrud; Nurrina, Rosli (Universiti Malaysia Pahang, 2018)
This research aims to examine on cooling efficiency of different type natural based material as a cooling pad for evaporative cooling system. Efficiency of direct evaporative cooling system mostly depends on the cooling pad and hence, the material used in the cooling pad plays a very vital role. Here, two types of natural based materials (activated carbon foam and luffa pad) were selected to be used as cooling pad. Those materials pad are then fabricated to fit into the evaporative cooling setup. Temperature, and humidity are the most important data in this experimental analysis. The readings of these terms are taken for each type of cooling pad using data logger and also, the further calculations are done based on these readings. The material of the cooling pad and the air flow rate are varied to observe the effect on their cooling efficiency. From the analysis, the ACF cooling pad shows better cooling efficiency compared to that of luffa pad.